Dielectric effects of bacterial cellulose (BC) impregnated with in-house synthesized carbon nanotubes (CNTs) - Adnan, Sharmeen; Awang Biak, Dayang Radiah (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2010)
Bacterial cellulose (BC) which was produced by Acetobacter xylinum has been identified as a potential biocomposite material. Various substances already introduced into BC pellicles for a wide range of application including carbon nanotubes (CNTs). In this study, CNTs, which were synthesized at low temperature, were impregnated in bacterial cellulose and have showed ionic conductivity. Dielectric properties analysis showed the dielectric conductivity value that varied according to the dispersion behaviour and resulted as 0.466 S/m for BC/CNTs-S0.05% whereas BC/CNTs-S0.02% and BC/CNTs-A0.02% value were 0.438 S/m and 0.229 S/m respectively. Spraying method applied in producing BC/CNTs performed very well with respect to better entanglement of bacterial cellulose and carbon nanotubes nanofibrils in terms of dielectric conductivity value.